Guerilla marketing : easy and inexpensive strategies for making big profits from your small business - Levinson, Jay Conrad, 1933-2013 (Boston : Houghton Mifflin Company, 2007)
An expanded and updated edition of the revolutionary marketing classic identifies the fastest growing markets, discusses recession strategies, modern consumers, targeted prospects, technology, and management; and furnishes new sections on Internet marketing, the use of new technologies, and cultivating repeat and referral business. Original.
Keywords: Marketing